2007
DOI: 10.1136/jech.2007.061937
|View full text |Cite
|
Sign up to set email alerts
|

Social problems, primary care and pathways to help and support: addressing health inequalities at the individual level. Part I: the GP perspective

Abstract: Objectives: This study aimed to describe social problems presented to general practitioners (GPs) in UK inner cities and GPs' responses; describe patients' help-seeking pathways; and consider how these pathways can be improved. Methods: The study involved a pilot survey and follow-up qualitative interviews with patients in two inner city areas in London and Salford in 2001-2. The pilot survey involved five practices in each locality. GPs completed questionnaires on 57 people presenting with social problems. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 20 publications
3
57
0
1
Order By: Relevance
“…This study was not designed to quantify how far the family types represent maltreatment-related concerns among all GPs in England but the families described by our participants are likely to be familiar within general practice. Descriptions of ‘on the edge’ and ‘stable at this point families’ were compatible with other descriptions of families and adults with social welfare problems in this setting 26. ‘On the edge’ narratives resonated with another well-known presentation: the ‘heart-sink’ patient.…”
Section: Discussionsupporting
confidence: 63%
“…This study was not designed to quantify how far the family types represent maltreatment-related concerns among all GPs in England but the families described by our participants are likely to be familiar within general practice. Descriptions of ‘on the edge’ and ‘stable at this point families’ were compatible with other descriptions of families and adults with social welfare problems in this setting 26. ‘On the edge’ narratives resonated with another well-known presentation: the ‘heart-sink’ patient.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies found that 82% of patients decreased their number of health professional consultations (Popay et al, 2007) and there was a reduction in medical prescriptions (Age UK, 2012). However, Grant et al (2000) reported little decease in primary care use.…”
Section: Changes In Health Service Usementioning
confidence: 99%
“…Part I of the paper focused on GPs’ perspectives on the social problems experienced by their patients and how they respond to these 1. Here we have described the wider help-seeking pathways followed by some of the patients included in the GP survey highlighting the complex and often long-term nature of the social problems presented to GPs; the resilience shown by people experiencing these social problems; the persistence with which they pursue help and advice; and the obstacles they face in seeking to manage their problems.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the pilot survey of general practice consultation is described elsewhere 1. Here we describe the qualitative study of help-seeking pathways.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation